1995
DOI: 10.1007/bf02736784
|View full text |Cite
|
Sign up to set email alerts
|

Three related brain nuclear receptors, NGFI-B, Nurr1, and NOR-1, as transcriptional activators

Abstract: Three related orphan nuclear receptors that are expressed in the brain, NGFI-B, Nurr1, and NOR-1, were studied to compare their function as transcriptional activators. NGFI-B was able to activate (in the absence of added hormone) in CV1 cells both an NGFI-B-responsive luciferase reporter gene (containing eight copies of a response element for NGFI-B upstream of a basal prolactin promoter driving the luciferase gene, NBRE(8)-LUC), a similar thyroid hormone-receptor-responsive reporter gene (TRE(3)-LUC), and a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 25 publications
1
71
1
4
Order By: Relevance
“…Thus, it appears that unlike in the immune system, NGFI-B and Nor-1 expressed in the striatum have distinct functions. It has been shown that Nor-1, unlike NGFI-B (Nur77) and Nurr1, cannot form heterodimers with members of the RXR family (Paulsen et al, 1995;Zetterström et al, 1996). This reinforces the possibility of an involvement of an NGFI-B/ RXR complex in the effects investiged here.…”
Section: Ngfi-b(+/+) Ngfi-b(-/-) Ngfi-b(+/+) Ngfi-b(-/supporting
confidence: 86%
See 1 more Smart Citation
“…Thus, it appears that unlike in the immune system, NGFI-B and Nor-1 expressed in the striatum have distinct functions. It has been shown that Nor-1, unlike NGFI-B (Nur77) and Nurr1, cannot form heterodimers with members of the RXR family (Paulsen et al, 1995;Zetterström et al, 1996). This reinforces the possibility of an involvement of an NGFI-B/ RXR complex in the effects investiged here.…”
Section: Ngfi-b(+/+) Ngfi-b(-/-) Ngfi-b(+/+) Ngfi-b(-/supporting
confidence: 86%
“…On the contrary, the effects of haloperidol on the expression of DYN (Figure 4a, b), c-fos (Figure 4c, d), and Nor-1 (Figure 4e, f), a close homologue of NGFI-B (Paulsen et al, 1995), are similar in WT and NGFI-B (À/À) mice. However, the effect of haloperidol on Nor-1 mRNA levels is significantly higher in NGFI-B-deficient mice compared to WT mice (Figure 4f).…”
Section: Neuroleptic-induced Catalepsy Is Strongly Reduced In Ngfi-b-mentioning
confidence: 89%
“…This observation suggests the possibility that Nur77 may alter Nurr1-dependent transcriptional activity in DA cells. The molecular and structural organization of Nur77 is very close to Nurr1, and it has been reported that both can interact with the same responsive elements (Maira et al 1999;Paulsen et al 1995;Perlmann and Jansson 1995). Thus, we might expect that induction of Nur77 would enhance Nur-dependent transcriptional activity in DA cells.…”
Section: Discussionmentioning
confidence: 89%
“…In humans, the NR4A subfamily of orphan nuclear receptors (NRs) comprises three members: NGFI-B (NR4A1), also referred as NAK1, Nur77, ST-59, TR3 and eight others aliases [8]; NURR1 (NR4A2), and NOR1 (NR4A3). Monomeric, homodimeric, or heterodimeric NR4A receptors regulate target gene transcription from target sequences such as AAAGGTCA, termed NGFI-B response elements [9,10] in a cell type-and promoterdependent manner [8,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Monomeric, homodimeric, or heterodimeric NR4A receptors regulate target gene transcription from target sequences such as AAAGGTCA, termed NGFI-B response elements [9,10] in a cell type-and promoterdependent manner [8,[11][12][13]. In addition, NGFI-B and Nurr1 act on DR5 elements…”
Section: Introductionmentioning
confidence: 99%